Constructing gender and sexuality in the EFL classroom in Poland: Textbook construction and classroom negotiation? - Pawelczyk, Joanna; Pakuła, Łukasz (Routledge, 2015)
Poland, as a young conservative democracy, is witnessing an unprecedented amount of public debate where ‘gender’ and ‘sexuality’ figure prominently. Both, however, tend to be perceived as foreign imports and thus fiercely contested. Consequently, the role of English as a Foreign Language (EFL) materials as well as teachers as potential mediators of markedly different Anglophone socio-politics is of paramount importance. What is more, the only Polish research examining the portrayal of women in EFL materials is that by Jaworski (1986), who exposed the abundance of sexism in EFL textbooks available in Poland at that time. Regrettably, ‘sexuality’ as a culturally (but not linguistically) important identity category was not addressed or recognised in the broad Polish educational context until 2012 (Świerszcz 2012). This chapter reports on two studies conducted as part of the research project entitled “Investigating Gender and Sexuality in the ESL classroom: Raising publishers', teachers' and students' awareness”. The aim of the first study was to qualitatively scrutinize the discursive and multimodal construction of gender, gender relations, and sexuality in two leading illustrated Primary School EFL textbooks in Poland, along with the accompanying workbooks and teacher’s books. To this end the analytical methods of Feminist Critical Discourse Analysis (Fairclough 1989; Lazar 2005, 2014), Multimodal Discourse Analysis (see e.g. Giaschi 2000; Guo 2004; O’Halloran 2004; Kress and Van Leeuwen 2006) and the concept of critical heteronormativity (Motschenbacher 2010, 2011) were utilized. The analyses focused on the representation of the social roles of men and women, boys and girls in EFL materials. They also demonstrated different textual manifestations of heteronormativity. ‘Gender critical points’ (Sunderland et al. 2002) – identified in the first study - were drawn on in the second study. We also extended Sunderland et al.’s (2002) concept by introducing the notion of ‘gender-emerging points’, which we believe enriches the analytical apparatus by highlighting the dynamic character of classroom interactions and thus the central role of teachers. Here we used audio-recorded primary school classroom interactions to demonstrate how the identified ‘gender critical points’ are addressed and how ‘gender-emerging points’ surface and/or are made (ir-)relevant in the classroom setting. Thus the analysis focused on gendered ‘talk around the text’ emerging in teacher-student interactions to explore negotiation, challenge and/or rejection and ‘uptake’ of gender roles and discourse. To this end methods and insights from critical linguistic analysis were used along with Sunderland’s (this volume) agenda for future research on gender representation in foreign language textbooks.
Keywords: gender and sexuality in education; gender and language; sexuality and language; hidden curriculum; ideology of gender; Polish context; sexism in EFL; heteronormativity; classroom discourse; homophobia in Poland; Critical Discourse Analysis; Multimodal Discourse Analysis